Structural Evolution of an Organic Semiconducting Molecule onto a Soft Substrate. Issue 8 (19th February 2016) - Martínez‐Tong, Daniel E.; Ruzié, Christian; Geerts, Yves H.; Sferrazza, Michele
Abstract: The structural organization and evolution of the organic semiconducting molecule 2, 7‐dioctyloxy[1]benzothieno[3, 2‐ b ]‐benzothiophene on a soft matrix is studied. Thin films of a blend formed from polystyrene and the molecule were prepared by spin‐coating onto silicon substrates, which were subsequently studied by using a combination of microscopy and scattering techniques. The organic semiconducting molecule segregated to the surface and developed a phase with a different structure to the bulk, as in the case of a substrate induced phase observed previously. Under a solvent vapor annealing procedure, the growth of micrometer‐sized tetragonal crystals onto the polymer surface was observed, which was not evidenced for the silicon substrates. Abstract : Growing semiconducting crystals : The influence of a soft polymer substrate on the crystalline growth of a [1]benzothieno[3, 2‐ b ]benzothiophene (BTBT) derivative is studied. A crystalline phase, with a structure different from the bulk one, is observed. By treating the samples in a solvent atmosphere, micrometer‐sized tetragonal crystals are grown on the polymer surface.